The relationship among maternal, household, socio economic characteristics and household food security in Aceh – Indonesia - Srinita Srinita (Proceedings of AICS - Social Sciences, 2017)
The objective of the study is to investigate the Relationship between Maternal, Household, and Socio-Economic Characteristics on Household Food Security in Aceh-Indonesia. The data used are cross-section data, secondary data from the Economic Census of Indonesia in 2016 (BPS, 2016), from 23 districts / cities. The central message of the present empirical analysis is that relatively simple indicators perform well in locating food security. The analysis proves that mother’s age has a significant effect on average calorie intake at the household level. This may be due to the fact that mother’s age plays an important role in the provision of proper food to her family. Higher-aged mothers can understand better about the food quality and requirement for the family as compared to low-aged mother. Environmental factors like access to safe water and better sanitation facilities within housing premises indirectly enhance the absorptive capacity of available food intake. Thus environmental factors could play an important role in food security through calorie intake, irrespective of economic status of the household. This analysis further strengthens the earlier findings that higher food intake availability alone may not lead to improved health outcome, unless measures are taken to improve access to safe water and sanitation. Contribution of dependency ratio in per capita calorie intake also appeared to be significant in this study. This shows that high dependency ratio reduces the per capita calorie intake due to a larger share in food items among a household.